Enhancing storage stability of smoke-flavored horse mackerel filets using natural extracts as preservatives - Barros, Diana; Nova, Paulo; Cunha, Sara; Monteiro, Vitor; Fernandes, Élia; Pereira-Pinto, Ricardo; Barbosa, Carla; Pintado, Maria; Gomes, Ana; Vaz-Velho, Manuela (Frontiers in Sustainable Food Systems, 2023)
The Atlantic horse mackerel (Trachurus trachurus) is a globally favored fish due to its abundance, nutritional value, and affordability, but it faces quality preservation challenges. To address this, this study aimed to enhance its value by creating low-salt smoked products with natural bioactive compounds from seafood and forest sources. The fish filets were divided into four groups: one as a control, and the others were treated with various bioactive extract solutions, specifically pine bark, mussels, and microalgae. After 15 days of storage at 4°C, significant differences in properties were observed. Moisture and salt had an inverse relationship, with decreasing moisture and pH over time. Oxidation levels remained acceptable, although sensory quality was affected by storage. Microbiological analysis uncovered high contamination levels in certain samples at specific points in time, although no pathogens such as Salmonella spp. or Listeria monocytogenes were detected. While microalgae extract was the most powerful antioxidant, its performance was hampered by the poor sensory scores. On the other hand, pine bark extract was the most acceptable from a sensory point of view and revealed some antimicrobial inhibition. Using natural antioxidants provides an appealing solution for consumers seeking products with clean labels.